Strategi Komunikasi Tim Satuan Tugas (Satgas) Dalam Menangani Pandemi Covid-19 Di Desa Panjeng, Kecamatan Jenangan, Kabupaten Ponorogo - Muhammad Anwar Tamami; Andhita Risko Faristiana (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Corona virus disease 2019 or Corona Virus Disease-19 (Covid-19) is a respiratory tract infection caused by a type of corona virus. Another name for this disease is Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV2). In just a few months, the spread of this disease has spread to various countries, both in Asia, America, Europe, and the Middle East and Africa. The increase in the number of Covid-19 cases is increasing because it spreads so quickly, Covid-19 spreads and can infect a person regardless of age, therefore a communication strategy is needed to prevent the transmission of Covid-19 by the central government, regional governments and the government village. The importance of this communication strategy in tackling the corona virus is to minimize and prevent the spread of the virus in affected areas.Panjeng Village, Jenangan District, Ponorogo Regency, is one of the areas affected by the Covid-19 pandemic. In communicating with the Panjeng village community, the Covid-19 Task Force has an effective communication strategy in carrying out the process of handling the Covid-19 pandemic. Therefore, the purpose of this research is to find out the communication strategy of the Covid-19 task force in dealing with the Covid-19 pandemic in Panjeng Village. In this study, researchers used communication strategy theory according to Mintzberg and Waters, regarding the stages of communication strategy, namely communication strategy planning, communication strategy implementation, and communication strategy evaluation. The research method used in writing this thesis is using a descriptive qualitative research method and the type of research in the field, namely the method of observation, interviews, and documentation. Then the researcher analyzed the data using the reduction method, data presentation, and verification (conclusion) to obtain the expected data.